The Politics of Dating Apps Gender, Sexuality, and Emergent Publics in Urban China - Chan, Lik Sam (Information Society Series, 2021)
An examination of dating app culture in China, across user demographics-straight women, straight men, queer women, and queer men. In this exploration of dating app culture in China, Lik Sam Chan argues that these popular mobile apps are not merely a platform for personal relationships but also an emerging arena for gender and queer politics. Chan examines the opportunities dating apps present for women's empowerment and men's performances of masculinity, and he links experiences of queer dating app users with their vulnerable position as sexual minorities. He finds that dating apps are both portals to an exciting virtual world of relational possibilities and sites of power dynamics that reflect the heteronormativity and patriarchy of Chinese society. Drawing on in-depth interviews with urban users of such dating apps as Momo, Tantan, Blued, Aloha, Rela, and Lesdo, Chan proposes "networked sexual publics" as a unifying concept to capture the dynamics of dating app culture. Devoting a chapter to each of four publics-straight women, straight men, queer men, and queer women-Chan documents how relationships are shaped and transfigured by this emerging technology. He considers whether dating apps can be a feminist tool; explores straight men's self-presentation on the apps and their interactions with women they meet there; discusses the constant cycle of deleting and installing the same apps seen among queer men; and examines how popular lesbian dating apps may connect queer women to their communities. Finally, Chan maps possible paths for future intersectional, queer, and feminist scholarship on emerging communication technologies.